(untitled) (Archives of Criminology, 2008)
The issues addressed in the article concern the genetic causes of behaviour inherent in human nature, which constitute a barrier to manifestations of human transgression. The author introduces the issue of characteristics of human nature and sociobiology, which is the science of biological grounds for social behaviour. The main purpose of the paper is to show that sociobiological and neurobiological research indicate that human morality is an innate feature of human nature with a genetic origin. Andrzej Mościkier looks at the innate features of human nature, such as egoism and drive for domination, which lead to violence and aggressive behaviour and which have a genetic basis. Among other natural negative human traits, the author lists malice and deceit, which surely have a criminogenic character. In the text, Mościkier tries to determine whether counteracting the natural negative tendencies of human nature lies within the sociocultural sphere or is merited by the evolution of the human species. To this end, he presents an in-depth analysis of the phenomena of kin altruism and reciprocal altruism. Then, he discusses the theory of inborn fundamentals of morality, which is based on the conviction that kin altruism is the genetic basis of morality and a derivative of such feelings as empathy, compassion, or respect for another human being. When summarising his text, Mościkier emphasises that crime is a product of both nature and culture (upbringing). A human being is rather a moral being by nature and exceptional cases of lack of morality are connected with dysfunctions of the individual’s nervous system. The human conscience, on the other hand, is a control mechanism that deters the perpetration of criminal acts and has a genetic background.